2020
DOI: 10.1111/1754-9485.13072
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of patients with conserved breast cancer treated with adjuvant hypofractionated prone breast intensity‐modulated radiation therapy

Abstract: Introduction: New techniques for adjuvant radiation therapy after breast conservation include prone positioning, hypofractionation and intensity-modulated radiation therapy (IMRT). Long-term evaluations of this combination are lacking, and we report our own experience. Methods: Patients with invasive breast cancer followed for a minimum 36 months post-IMRT were eligible. Dose used was 40 Gray in 15 fractions over 3 weeks to the whole breast via forward-planned prone, whole breast IMRT. A 10 Gy in 5 fraction su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We report efficacy and toxicity outcomes that are very comparable to those reported in major metropolitan Australian centres. This is not surprising to us, as we have previously demonstrated excellent efficacy and toxicity outcomes for a number of other cancer types when using IMRT and VMAT 15–17 …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We report efficacy and toxicity outcomes that are very comparable to those reported in major metropolitan Australian centres. This is not surprising to us, as we have previously demonstrated excellent efficacy and toxicity outcomes for a number of other cancer types when using IMRT and VMAT 15–17 …”
Section: Discussionmentioning
confidence: 53%
“…This is not surprising to us, as we have previously demonstrated excellent efficacy and toxicity outcomes for a number of other cancer types when using IMRT and VMAT. [15][16][17] Furthermore, the treatment of anal cancer is guided by consensus-driven protocols such as eviQ and the Australasian Gastrointestinal Trials Group guidelines, which enable all cancer centres to offer standardised, peer-reviewed, high-quality treatment whose outcomes can be compared for quality control. We contend that, with appropriate experience and support services, regional cancer centres can deliver exceptional results.…”
Section: Discussionmentioning
confidence: 99%
“…Although cardiac risk reduction strategies such as the role of active-breathing modalities (22), patient positioning (23,24), and accelerated partial breast irradiation (25) are discussed, few efforts in randomized controlled trials have validated the cardiac-sparing techniques or looked into the early response of cardiac substructures to breast RT. The fact that 3 patients received a higher mean heart dose in free-breathing RT but showed no differences in other dosimetric parameters of the heart and its substructures implies that DIBH RT can achieve better sparing in terms of the whole heart than free-breathing RT can.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment in a prone position allows the breast tissue to sag down, which increases the tumor-rib distance, and, additionally, a prone position reduces the absolute rib volume receiving a certain radiation dose. Notably, a study of patients who underwent breast radiotherapy in the prone position reported no RIRF occurrence [26]. However, a prone position is less effective for chest wall irradiation in patients without remnant breast tissue and is unsuitable for treating advanced-stage patients requiring the inclusion of regional lymph nodes.…”
Section: Discussionmentioning
confidence: 99%